Adherence with the standard treatment regimen for the treatment of COVID-19 patients in Bangabandhu Sheikh Mujib Medical University - Sharmin, Elora; Ahmed, Md Sharfuddin; Amin, Md Rasul; Hasan, Md Nazmul; Papia, Sayeda; Ahmed, Sheikh Foyez; Quader, Rezwanul (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
The present study was conducted to evaluate the adherence to standard treatment regimen in Bangabandhu Sheikh Mujib Medical University (BSMMU) for the treatment of corona virus disease 19 (COVID-19) patients. The study assessed the awareness of prescribers, adherence to treatment guidelines and reasons for non-adherence. A questionnaire survey was conducted followed by a retrospective and prospective medical review and in-depth interview. The study revealed that 79.9% of key prescribers are aware of treatment guidelines. Adherence was 28.4% in moderate cases and 53.3% in severe cases and difference was highly statistically significant (p<0.001). Adherence in moderate cases was highest in patients with hypertension (43.3%) and lowest in bronchial asthma (16.6%). Adherence in severe cases was highest with diabetes (80%) and lowest in bronchial asthma (20 %). In COVID-19 patients, the adherence was highest with International Guideline (96%), followed by institutional Guideline (74.6%) and National Guideline (23.5%). There is significant variation in extent of adherence in different age group of patients, co-morbidities and categories of guidelines. BSMMU J 2021; 14 (COVID -19 Supplement): 13-18